We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
256
1
avatar

6.2e^(0.64t) = 3e^(t+1)

 Jan 25, 2018
 #1
avatar+18274 
0

Divide both sides by 3 to get

2.06667 e^.64t = e^(t+1)      divide by  e^.64t

 

2.06667 = e ^(t+1) / e^(.64t)     take ln of both sides

.72594 = t+1   - .64t)

-.2740  = . 36 t

t =-.7613

 Jan 25, 2018

14 Online Users

avatar